Eksplorasi Dan Identifikasi Keanekaragaman Anggrek Epifit Di Kawasan Gunung Cibunar Blok Beser Rancakalong Sumedang - Lia Amalia; Adi Sopian; Kovertina Rakhmi Indriana (Paspalum: Jurnal Ilmiah Pertanian, 2023)
This article aims to determine the potential of epiphytic orchids by exploring, identifying and studying the diversity of epiphytic orchids. The method used is exploration and sampling using purposive sampling with an exploratory area of 3,300 m2. Found 1037 individuals from 18 species obtained 14 genera. The highest density value is the species Dendrobium mutabile with a value of 0.0785 individuals/m2 and a relative density of 24.9759%. Dendrobium mutabile had the highest frequency value of 7.8485 and a relative frequency of 24.9759% which was found in 22 out of 30 plots. The Importance Value Index obtained the highest value for the orchid species Dendrobium mutabile with an IVI value of 499,518, thus it can be said that Dendrobium mutabile dominates. There were 12 host trees encountered during the exploration, namely (Tectona grandis), (Arenga pinnata), (Pinus merkusii), (Ficus benjamin), (Alstonia scholaris), (Coffee canephora pierrakoppi), (Ceiba pentandra), (Swietenia macrophylla), (Mangifera foetida), (Syzygium aromaticum), (Citrus hystrix), (Cocos nucifera L).